2014
DOI: 10.1371/journal.pone.0109706
|View full text |Cite
|
Sign up to set email alerts
|

Linking of Primary Care Records to Census Data to Study the Association between Socioeconomic Status and Cancer Incidence in Southern Europe: A Nation-Wide Ecological Study

Abstract: BackgroundArea-based measures of economic deprivation are seldom applied to large medical records databases to establish population-scale associations between deprivation and disease.ObjectiveTo study the association between deprivation and incidence of common cancer types in a Southern European region.MethodsRetrospective ecological study using the SIDIAP (Information System for the Development of Research in Primary Care) database of longitudinal electronic medical records for a representative population of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 39 publications
6
42
1
Order By: Relevance
“…We found a higher risk of prostate cancer in the category of medium deprivation, and overall the lowest incidence of prostate cancer was observed in the least deprived category. A number of studies, using individual or area-based indicators of social position, reported a higher risk in those with a high socioeconomic status [6,[19][20][21], although other found no or negative associations, especially among African American men [22,23]. The high incidence in the most favored groups is generally attributed to a higher rate of screening, leading to the detection of indolent cases and overdiagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…We found a higher risk of prostate cancer in the category of medium deprivation, and overall the lowest incidence of prostate cancer was observed in the least deprived category. A number of studies, using individual or area-based indicators of social position, reported a higher risk in those with a high socioeconomic status [6,[19][20][21], although other found no or negative associations, especially among African American men [22,23]. The high incidence in the most favored groups is generally attributed to a higher rate of screening, leading to the detection of indolent cases and overdiagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Information collected included all the variables listed previously for the CPRD data . For the socioeconomic status the Medea Index was used with R and Q± as those with no information available on Medea Index, Q1 as the least deprived, and Q5 as the most deprived …”
Section: Methodsmentioning
confidence: 99%
“…It remains unclear whether high‐risk sexual behaviors known to influence the risk of developing HPV‐related oropharyngeal SCC are more likely to occur in family members of patients with HPV‐associated malignancies. Socioeconomic status, which is familial, has been associated with the risk of developing cervical cancer, likely through access to preventative care . However, again, it is unlikely that shared behaviors alone would result in elevated risks to relatives as distant as third‐degree.…”
Section: Discussionmentioning
confidence: 99%
“…Socioeconomic status, which is familial, has been associated with the risk of developing cervical cancer, likely through access to preventative care. 11 However, again, it is unlikely that shared behaviors alone would result in elevated risks to relatives as distant as third-degree. Given the ubiquitous nature of HPV exposure, 12 genetic susceptibility to HPV-related malignancies may well play a role.…”
Section: Discussionmentioning
confidence: 99%